Saturated Dissolved Oxygen Concentration in in situ Fragmentation Bioleaching of Copper Sulfide Ores - Huang, Ming-Qing; Zhang, Ming; Zhan, Shu-Lin; Chen, Lin; Xue, Zhen-Lin (Frontiers in Microbiology, 2022)
For now, in-situ fragmentation bioleaching has been a promising way to fulfill deep mining safely, environmental friendly and economically, where oxygen plays a critical role in microbial growth and mineral dissolution. To overcome this limitation, aeration was proposed with saturated dissolved oxygen concentration as an important indicator. Orthogonal experiments were conducted to measure saturated dissolved oxygen concentration at various temperature, pH and electrolyte (ferrous sulfate, ferric sulfate, copper sulfate and sulfuric acid) concentration conditions. Experimental data was analyzed by Python programming language and least square method to obtain a saturated dissolved oxygen concentration model. Results showed that temperature had the most significant effect on oxygen solubility, which was concluded by comparing the results of surface fitting based on least square method. At 30-40°C, the saturated dissolved oxygen concentration decreased faster as metal ions concentration increased. The conjoint effect of the five variables on oxygen solubility showed that pH was linearly negatively related to oxygen solubility. A mathematical model was also proposed to prediction the saturated dissolved oxygen concentration in in-situ fragmentation bioleaching of copper sulfide ores. The work enables the bioleaching processes to be modelled and controlled more effectively.